Research interests related to climate change - Anandhi, Aavudai (Kansas State University, 2012)
This research develops impact assessments of climate change projections by incorporating climate variables (including water (SF, P), Heat (T, SR), carbon dioxide, relative humidity and wind speed) into existing process based and black box models. Changes in Kansas climate will be reflected in both the mean values for rain fall, maximum, minimum, average, and diurnal temperature as well as extreme values for rain fall, and maximum and minimum temperature. Based on analysis of data from 23 centennial weather stations, the highest average monthly temperature during the summer season was from 1920-1949 for many locations. This indicates the dust bowl years can serve as a good proxy for the near future climate conditions. Long term trends for frost indices in Kansas have changed at both the beginning and end of the growing season with earlier last spring freeze events and later first fall freezes, although this is less consistent than the last spring freeze. Combined, these result in fewer frost days and a longer growing season. Further analysis will assess the impact of potential producer adaptations to these changes such as earlier planting dates in response to earlier last spring freeze events on biomass yield.
Keywords: Cropping systems; Crop models; Climate variables; Climate change